Neural pathways from hypothalamic orexin neurons to the ventrolateral preoptic area mediate sleep impairments induced by conditioned fear - Ma, Caifen; Zhou, Ning; Ma, Kang; Niu, Jiandong; Mi, Ting; He, Zhenquan; Wen, Yujun; Liu, Chunhong; He, Zhongyi; Niu, Jianguo (Frontiers in Neuroscience, 2023)
Fear and sleep impairments often co-exist, but the underlying mechanisms remain unclear. In the present study, the neural pathways by which conditioned fear induces sleep impairments were identified. The retrograde tracing technique was used to demonstrate the projections from the orexin-containing hypothalamic neurons to the ventrolateral preoptic area (VLPO). By combining retrograde tracing technique and immunofluorescence staining, we found that orexin-VLPO neural pathways are activated by conditioned fear. With optogenetics and cortical electroencephalography (EEG), it was observed that the optogenetic activation of orexin neurons or orexin-VLPO neural pathways significantly decreases sleep time and increases wakefulness time in mice with conditioned fear. A significant decrease in sleep time and an increase in wakefulness time were observed after the injection of orexin-A into the VLPO. The effects of orexin-A in the VLPO were blocked by a pre-administrated dual orexin receptor antagonist (DORA). The results suggest that neural pathways from hypothalamic orexin neurons to the VLPO mediate sleep impairments induced by conditioned fear.